Manifesto of the New Economy Institutions and Business Models of the Digital Society - Dolgin, Alexander (Springer Berlin Heidelberg : Imprint: Springer, 2012)
How do social networking services earn money? What is the "second hand of the market" and how does it operate? Why does society need so many different kinds of goods? What does happiness economics not reveal about happiness? What is the link between talent, success and "stardom"? What is the business development  model for the entertainment and media industry? What is emotional hysteresis? How can we measure cultural values? What is subjective time and how can it be made qualitative? What is club economics? You can find the answers to all these questions in the book. It describes the main trends in development of our digital society. It appeals to those who are curious about what will replace search engines, and how social networking services will evolve. It is about the profit from different forms of informational collaboration (crowdsourcing, collaborative filtering) and how it will affect the structure of the society and human pursuit for happiness.